The association of dietary spermidine with all-cause mortality and CVD mortality: The U.S. National Health and Nutrition Examination Survey, 2003 to 2014 - Wu, Huanyu; Wang, Jianing; Jiang, Hongyan; Liu, Xin; Sun, Xinyi; Chen, Yunyan; Hu, Cong; Wang, Zheng; Han, Tianshu; Sun, Changhao; Wei, Wei; Jiang, Wenbo (Frontiers in Public Health, 2022)
Background Current studies on the protective effects of dietary spermidine(Spd) on cardiovascular disease(CVD) are mainly limited to animal studies, and the relationship between dietary Spd and CVD mortality remains inconclusive. Objective This study aims to evaluate the association between dietary Spd intake and CVD and all-cause mortality. Methods A total of 23,894 people enrolled in the National Health and Nutrition Examination Survey(NHANES) from 2003 to 2014 were recruited for this study. Dietary intake of Spd from 11 specific food origins and total Spd was categorized into tertiles or quartiles. Cox-proportional hazard regression models were developed to evaluate the association of Spd intake with CVD and all-cause mortalities. Results Among the 23,894 participants, 2,365 deaths, including 736 deaths due to CVD, were documented. After adjustment for potential confounders, compared with participants in the lowest quartile, participants in the highest quartile of total Spd had a significantly lower risk of CVD mortality(HR=0.69, 95% CI: 0.52–0.92) and all-cause mortality(HR=0.70, 95% CI: 0.60–0.82); participants in the highest tertiles or quartiles of vegetable-derived Spd, cereals-derived Spd, legumes-derived Spd, nuts-derived Spd, and cheese-derived Spd had a lower risk of CVD mortality(HR vegetables-derived Spd=0.68, 95% CI: 0.54–0.86; HR cereals-derived Spd=0.75, 95% CI: 0.57–0.97; HR legumes-derived Spd=0.68, 95% CI: 0.52–0.88; HR nuts-derived Spd=0.66, 95% CI: 0.53–0.81; HR cheese-derived Spd=0.68, 95% CI: 0.52–0.88) and all-cause mortality(HR vegetables-derived Spd=0.73, 95% CI: 0.65–0.84; HR cereals-derived Spd=0.80, 95% CI: 0.69–0.93; HR legumes-derived Spd=0.70, 95% CI: 0.61–0.81;HR nuts-derived Spd=0.72, 95% CI: 0.64–0.81; HR cheese-derived Spd=0.70, 95% CI: 0.61–0.81) than those in the lowest tertiles or quartiles. Moreover, subgroup analysis showed consistent associations among the people with hypertension and hyperlipidemia. Conclusion Higher intake of dietary Spd is associated with decreased risk of CVD and all-cause mortality, and among specific food origins Spd, vegetables, cereals, legumes, nuts, and cheese derived Spd was associated with reduced CVD and all-cause mortality.